Secondary language impairment in posterior cortical atrophy: insights from sentence repetition - Ahmed, Samrah; Caswell, Josie; Butler, Christopher R.; Bose, Arpita (Frontiers in Neuroscience, 2024)
Introduction Posterior cortical atrophy (PCA) is a neurodegenerative syndrome characterized by progressive impairment in visuospatial and perceptual function linked to atrophy of the occipito-parietal cortex. Besides the salient visual impairment, several studies have documented subtle changes in language may also be present. Sentence repetition is a highly constrained linguistic task involving multiple linguistic and cognitive processes and have been shown to be impaired in other AD spectrum disorders, with little consensus on its relevance in PCA. This aim of this study was to further delineate the linguistic and cognitive features of impaired language in PCA using a sentence repetition task. Method Seven PCA patients and 16 healthy controls verbally repeated 16 sentences from the Boston Diagnostic Aphasia Examination. Responses were transcribed orthographically and coded for accuracy (percentage accuracy; percentage Correct Information Units; Levenshtein Distance) and for temporal characteristics (preparation duration (ms); utterance duration (ms); silent pause duration (ms); speech duration (ms); dysfluency duration (ms)). The potential modulating effects of attentional control and working memory capacity were explored. Results PCA patients showed lower overall accuracy with retained semantic content of the sentences, and lower phonological accuracy. Temporal measures revealed longer preparation and utterance duration for PCA patients compared to controls, alongside longer speech duration but comparable dysfluency duration. PCA patients also showed comparable silent pause duration to controls. Attentional control, measured using the Hayling sentence completion task, predicted accuracy of sentence repetition. Discussion The findings suggest that sentence repetition is impaired in PCA and is characterized by phonological, response planning and execution difficulties, underpinned in part by attentional control mechanisms. The emerging profile of language impairment in PCA suggests vulnerability of similar cognitive systems to other Alzheimer’s syndromes, with subtle differences in clinical presentation.